Karakteristik Desain Pembelajaran Inkarnatif: Studi Analisis Aksidensi Konsep Inkarnasi - Sugiono, Sandrakh; Hardori, Johni (Fakultas Ilmu Keguruan dan Pendidikan, Universitas Kristen Indonesia, 2022)
Learning Christian Religious Education must have different characteristics from learning other fields of science in addition to having the same characteristics. These different characteristics cannot come from the basics of education that are used in general, unless learning for Christian Religious Education is developed based on different learning model designs. The development of different learning model designs must also be based on concepts, theories, philosophy, or theology, which have differences from the development of other learning model designs. The development of the learning design can be done by analyzing the contents of the concept of the incarnation of the Word of God to find the characteristics of its occurrence. The characteristics of the accidental incarnation of the Word of God then became the characteristics of incarnative learning designs for Christian Religious. The results of accidental analysis of the concept of the incarnation of God's Word are as follows: 1) divine and human dimensions, 2) distinctive, 3) communicative-participatory, 4) contextual-multicultural, 5) lifetime, 6) trinity-centric, 7) ethical- theocentric, 8) ecclesiastical and 9) the values of the kingdom of God. AbstrakPembelajaran Agama Kristen haruslah memiliki karakteristik yang berbeda dengan pembelajaran bidang-bidang ilmu lainnya di samping adanya karakteristik yang sama. Karakteristik yang berbeda tersebut tidak dapat berasal dari dasar-dasar pendidikan yang digunakan pada umumnya, kecuali pembelajaran bagi Agama Kristen dikembangkan berdasarkan desain model pembelajaran yang berbeda. Pengembangan desain model pembelajaran yang berbeda harus pula berdasarkan konsep, teori, filsafat, atau teologi, yang memiliki perbedaan dengan pengembangan desain model pembelajaran lainnya. Pengembangan desain pembelajaran tersebut dapat dilakukan dengan menganalisis isi konsep inkarnasi Firman Allah hingga didapati ciri-ciri aksidensinya. Ciri-ciri aksidensi inkarnasi Firman Allah tersebutlah yang kemudian menjadi karakteristik desain pembelajaran inkarnatif bagi Agama Kristen. Hasil analisis aksidensi terhadap konsep inkarnasi Firman Allah sebagai berikut: 1) berdimensi ilahi dan insani, 2) khas, 3) komunikatif-partisif, 4) kontekstual-multikutural, 5) seumur hidup, 6) trinitas-sentris, 7) etis-teosentris, 8) eklesiatif dan 9) nilai-nilai kerajaan Allah.